2022
DOI: 10.12775/jehs.2022.12.07.101
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-neuro-endocrine accompaniments of individual variants of nitrogenous metabolites exchange

Abstract: Background. Earlier we showed, by constructing regression models, that plasma nitrogenous metabolites (uric acid, urea, creatinine and bilirubin) are able to influence the state of the trait anxiety, autonomic and central nervous and endocrine systems. In this study of the same cohort, other methodological approaches were used. Materials and Methods. The object of observation were almost healthy volunteers: 30 females (30÷76 y) and 31 males (24÷69 y). In basal conditions determined plasma levels of nitrogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The object of observation were employees of the clinical sanatorium "Moldova" and PrJSC "Truskavets' Spa": 31 males (24÷69 y) and 30 females, from among them 18 postmenopausal (48÷76 y) and 12 of reproductive age (30÷45 y). The volunteers were considered practically healthy (without a clinical diagnosis), but the initial testing revealed deviations from the norm in a number of parameters of the neuro-endocrine-immune complex as a manifestation of maladaptation [4,5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The object of observation were employees of the clinical sanatorium "Moldova" and PrJSC "Truskavets' Spa": 31 males (24÷69 y) and 30 females, from among them 18 postmenopausal (48÷76 y) and 12 of reproductive age (30÷45 y). The volunteers were considered practically healthy (without a clinical diagnosis), but the initial testing revealed deviations from the norm in a number of parameters of the neuro-endocrine-immune complex as a manifestation of maladaptation [4,5].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to routine parameters, Shannon's CE [18] Entropy of HRV and EEG were calculated [9,15]. See the previous articles for details [3][4][5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The object of observation were employees of the clinical sanatorium "Moldova" and PrJSC "Truskavets' Spa": 31 males (24÷69 y) and 30 females, from among them 18 postmenopausal (48÷76 y) and 12 of reproductive age (30÷45 y). The volunteers were considered practically healthy (without a clinical diagnosis), but the initial testing revealed deviations from the norm in a number of parameters of the neuro-endocrineimmune complex as a manifestation of maladaptation [4,6].…”
Section: Methodsmentioning
confidence: 99%
“…Earlier we found that plasma uric acid and urea causes modulating effects on neuro-endocrine parameters, as well as reactive anxiety, but these effects are significantly different in men and women of different ages [4][5][6][7]14].…”
Section: Introductionmentioning
confidence: 99%